2008
DOI: 10.1021/jo702310g
|View full text |Cite
|
Sign up to set email alerts
|

Rigid Multivalent Scaffolds Based on Adamantane

Abstract: We present two new synthetic strategies to rigid multivalent scaffolds of the general structure 1 based on adamantane. Both routes start from arylated adamantane derivatives and give the target compounds 12 and 18 in 5 and 7 steps, respectively. These scaffolds have been designed for the assembly of multivalent binders for cell surface epitopes. The adamantane nucleus exposes three carboxylic acid groups in a well defined tripodal geometry for conjugation of targeting ligands. In addition, an amino group at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 43 publications
0
43
0
Order By: Relevance
“…Building multiple attachment points on the surface of diamondoids may be useful for manufacturing diamond nanowires, [47] cell surface binders, [48] or for the construction of strong self-assembled monolayers on gold surfaces. [49,50] Recently we prepared several disubstituted triamantanes and [121]tetramantanes and demonstrated that, although kinetically controlled disubstitutions lead to complicated mixtures of isomers, thermodynamically controlled transformations are rather selective.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…Building multiple attachment points on the surface of diamondoids may be useful for manufacturing diamond nanowires, [47] cell surface binders, [48] or for the construction of strong self-assembled monolayers on gold surfaces. [49,50] Recently we prepared several disubstituted triamantanes and [121]tetramantanes and demonstrated that, although kinetically controlled disubstitutions lead to complicated mixtures of isomers, thermodynamically controlled transformations are rather selective.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…Adamantane, being the simplest and the most readily available of them attracts attention for its rigidity, relatively low molecular volume and lipophilicity [2][3][4]. Functionalized adamantanes find use in pharmaceutical applications [5][6][7], polymer synthesis [8], design of nanostructured materials [9,10], ionic liquids [11] and coordination chemistry [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Additional benefits arise from the rigidity of the diamondoid cages allowing construction of various three-dimensional structures with well-defined and predictable topologies [5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…](PF 6 ) 2[28] by applying the same experimental conditions as for the related complex [Cu(bipy)(COD)]PF6 …”
mentioning
confidence: 99%